2017
DOI: 10.18203/2320-6012.ijrms20172442
|View full text |Cite
|
Sign up to set email alerts
|

A study evaluating the awareness among general population towards common medical emergencies

Abstract: Background: Basic life support has been found to be lifesaving in common medical emergencies. The level of awareness about emergency care in general population and the approach of the common people with regards to common medical emergencies is an important determinant of positive outcome.Methods: This study was conducted in 445 participants randomly selected from visitors of our outpatient department, to study the awareness in general public about the medical emergencies and basic life support skills.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Similar to the results of our study, only 16% of the respondents would check for responsiveness in an unconscious patient. The results of this study showed awareness about common medical emergencies is low in the general public and there is a need to devise strategies to improve this awareness [ 11 ]. Besides BLS training in adults, many studies have supported the need for early awareness and training of Basic Life Support and resuscitation techniques in school children [ 12 - 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of our study, only 16% of the respondents would check for responsiveness in an unconscious patient. The results of this study showed awareness about common medical emergencies is low in the general public and there is a need to devise strategies to improve this awareness [ 11 ]. Besides BLS training in adults, many studies have supported the need for early awareness and training of Basic Life Support and resuscitation techniques in school children [ 12 - 14 ].…”
Section: Discussionmentioning
confidence: 99%